Proof-of-Principle Study Suggesting Potential Anti-Inflammatory Activity of Butyrate and Propionate in Periodontal Cells - Santos, Ana Flávia Piquera [UNESP] (2022)
Short-chain fatty acids (SCFAs) are potent immune modulators present in the gingival crevicular fluid. It is therefore likely that SCFAs exert a role in periodontal health and disease. To better understand how SCFAs can module inflammation, we screened acetic acid, propionic acid, and butyric acid for their potential ability to lower the inflammatory response of macrophages, gingival fibroblasts, and oral epithelial cells in vitro. To this end, RAW 264.7 and primary macrophages were exposed to LPSs from Porphyromonas gingivalis (P. gingivalis) with and without the SCFAs. Moreover, gingival fibroblasts and HSC2 oral epithelial cells were exposed to IL1β and TNFα with and without the SCFAs. We report here that butyrate was effective in reducing the lipopolysaccharide (LPS)-induced expression of IL6 and chemokine (C-X-C motif) ligand 2 (CXCL2) in the RAW 264.7 and primary macrophages. Butyrate also reduced the IL1β and TNFα-induced expression of IL8, chemokine (C-X-C motif) ligand 1 (CXCL1), and CXCL2 in gingival fibroblasts. Likewise, butyrate lowered the induced expression of CXCL1 and CXCL2, but not IL8, in HSC2 cells. Butyrate further caused a reduction of p65 nuclear translocation in RAW 264.7 macrophages, gingival fibroblasts, and HSC2 cells. Propionate and acetate partially lowered the inflammatory response in vitro but did not reach the level of significance. These findings suggest that not only macrophages, but also gingival fibroblasts and oral epithelial cells are susceptive to the anti-inflammatory activity of butyrate.